Arus Informasi Mengenai Sekolah Tinggi Agama Islam Negeri Jember Dalam Menarik Minat Calon Mahasiswa: The Flow of Information About the State Islamic Institute of Jember in Attracting Prospective Students - Muhibbin Muhibbin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
Despite various promotional programmes, STAIN Jember has not seen a significant annual increase in new student enrolment, suggesting suboptimal use of mass media in its socialisation processes. Drawing on communication theory and information diffusion models, this study investigates the volume of information received by prospective students, their information sources, the media channels used, and existing barriers. A survey was conducted, distributing questionnaires to 600 senior high school students across Jember, Situbondo, and Banyuwangi, selected through proportional cluster sampling. The findings reveal that although prospective students actively use television, radio, newspapers, and the internet to meet their information needs, STAIN Jember remains heavily reliant on brochures and banners, with 63% of respondents never having received an enrolment brochure. Furthermore, 57.2% expressed interest in enrolling, yet 64.5% never actively sought information about the institution, indicating a critical information gap. The study concludes that ineffective socialisation, limited use of mass media, and a lack of student involvement in campus activities exacerbate this asymmetry. It is recommended that STAIN Jember establish formal collaborations with the Department of Religious Affairs and the Department of Education, optimise multi-channel media strategies, and involve high school students in campus events to enhance information accessibility and institutional appeal. Meskipun memiliki berbagai program promosi, STAIN Jember belum mengalami peningkatan signifikan dalam jumlah pendaftar mahasiswa baru setiap tahunnya, yang mengindikasikan pemanfaatan media massa yang belum optimal dalam proses sosialisasi. Berdasarkan teori komunikasi dan model difusi informasi, penelitian ini menyelidiki volume informasi yang diterima calon mahasiswa, sumber informasi, saluran media yang digunakan, serta hambatan yang ada. Metode survei diterapkan dengan menyebarkan kuesioner kepada 600 siswa SLTA di Jember, Situbondo, dan Banyuwangi, yang dipilih melalui teknik proportional cluster sampling. Temuan menunjukkan bahwa meskipun calon mahasiswa aktif menggunakan televisi, radio, koran, dan internet untuk memenuhi kebutuhan informasi mereka, STAIN Jember masih sangat bergantung pada brosur dan spanduk, dengan 63% responden tidak pernah menerima brosur pendaftaran. Lebih lanjut, 57,2% menyatakan berminat mendaftar, tetapi 64,5% tidak pernah secara aktif mencari informasi tentang STAIN Jember, yang menunjukkan kesenjangan informasi yang kritis. Penelitian menyimpulkan bahwa sosialisasi yang tidak efektif, keterbatasan penggunaan media massa, dan kurangnya keterlibatan siswa dalam kegiatan kampus memperparah asimetri ini. Direkomendasikan agar STAIN Jember menjalin kerja sama formal dengan Departemen Agama dan Dinas Pendidikan, mengoptimalkan strategi multi-channel media, serta melibatkan siswa sekolah menengah dalam kegiatan kampus untuk meningkatkan aksesibilitas informasi dan daya tarik institusi.